Modeling and Characterization for Microstrip Filters in the Manufacturing Process through the Unscented Transform and Use of Electromagnetic Simulators - Abraham E. Ortega Paredes; Leonardo R. A. X. de Menezes; Humberto Abdalla; Ivan N. A. Romani (Modelling and Simulation in Engineering)
This paper presents the unscented transform (UT) applied to uncertainty modeling of manufacturing tolerances at the design stage of microwave passive devices. The process combines the UT with electromagnetic simulations and assumes that the numerical sources of error are negligible in comparison to the imperfections due to the manufacturing process. The technique was validated with the simulation, construction, and test of several sets of identical microstrip filters with very good results. Although the combination of UT and electromagnetic simulators was presented for microstrip filters, it can also be used for different types of microwave devices.